Impact of trade liberalization on Indonesian broiler competitiveness - Nurfadillah, S.; Rachmina, D.; Kusnadi, N. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
International trade has been growing rapidly and requires high competitiveness. Broiler industry is one of the sectors that might be threatened by trade liberalization. This study aims to analyze the competitiveness and government policies impact on the broiler competitiveness in actual and free trade condition. This research was conducted in Bogor and Subang using survey method. The sample consisted of 30 local farmers selected by random sampling and an integrated company selected purposively. Further data is analyzed using Policy Analysis Matrix (PAM). Privat Cost Ratio (PCR) and Domestic Resource Cost Ratio (DRCR) analysis showed that small farm has a competitive advantage, but does not have a comparative advantage. While the production by integrated company has comparative and competitive advantages. The policy analysis indicates that overall policies is protective and give benefit to producers. There are three scenarios that are used to portray free trade: reduction in import tariffs, interest rates, and logistics costs. The implementation of free trade will reduce competitiveness in actual price but increase competitiveness in the undistorted market condition.